Transformational Leadership and Performance-Based Policy Implementation in A Post-Conflict Private University: Evidence from Timor-Leste - Salustiano Quintao de Carvalho; Suwaib Amiruddin; Titi Stiawati (Syntax Corporation, 2026)
Higher education institutions in post-conflict countries face complex challenges in rebuilding governance systems, improving academic quality, and ensuring effective administrative performance. The adoption of performance-based policies has become a strategic approach to strengthen accountability and institutional effectiveness; however, its successful implementation depends largely on leadership capacity. In this context, transformational leadership is considered a critical factor in translating formal policies into meaningful organizational practices. This study aims to examine how transformational leadership supports the implementation of performance-based policies in a post-conflict private university setting, focusing on Universidade Oriental Timor Lorosa’e (UNITAL), Timor-Leste. This research employed a qualitative descriptive case study design. Data were collected through semi-structured interviews with 18 institutional stakeholders, participant observation, and analysis of governance and quality assurance documents. The findings demonstrate that transformational leadership has reinforced formal performance-based structures, particularly in strategic planning, administrative coordination, and internal quality assurance processes. However, policy enactment remains largely hierarchical and compliance-oriented, with limited stakeholder participation, weak integration into academic development practices, and inconsistent use of performance evaluation outcomes. Consequently, performance-based governance has improved procedural order but has not yet fostered sustained academic innovation, organizational learning, or collective ownership. This study contributes to leadership and governance scholarship by providing empirically grounded insights from a post-conflict higher education context and highlights the need to integrate performance-based systems with participatory and relational leadership practices to support meaningful institutional transformation.